Pre-proposal for the Integrative CRP on Climate Change, Agriculture and Food Security (CCAFS) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Pre-proposal submitted to the CGIAR Consortium in August 2015. Climate change will have far-reaching consequences for agriculture and natural resources – demanding a response that integrates food security, adaptation and mitigation, and puts greatest investment towards poor agriculture-dependent people whose livelihoods are most at risk. The overall purpose of CCAFS is to marshal the science and expertise of CGIAR and partners to catalyse positive change towards climate-smart agriculture, food systems and landscapes. CCAFS Phase II builds directly on the experience of CCAFS Phase I (including Extension Phase). CCAFS will be comprised of four Flagships: F1 on Climate-Smart Practices and Portfolios; F2 on Climate Information Services and Climate-Informed Safety Nets; F3 on Low Emissions Development; and F4 on Food System Governance under Climate Change.